Effects of soybean intercropping density on photosynthetic characteristics and disease resistance in tobacco - Liu, Xianglu; Hu, Yanxia; Yang, Chengwei; Li, Juan; Lu, Chunzhi; Tian, Nengfei; Zhou, Haiyang; Jin, Shuangzhen; Su, Jiaen; Wang, Dexun; Xu, Changhui; Huang, Yukai; et al. (Frontiers in Plant Science, 2025)
BackgroundIntercropping tobacco with soybean is a sustainable approach to improve resource use efficiency and crop resilience. However, the optimal soybean planting density for maximizing the physiological and protective benefits to tobacco remains unclear.MethodsA field experiment was conducted in Yunnan Province, China, including five treatments: tobacco monoculture and four tobacco–soybean intercropping densities. Photosynthetic parameters, carbon and nitrogen metabolism, defense-related physiology, and leaf chemical composition were measured across key growth stages.ResultsIntercropping density significantly affected photosynthetic and metabolic performance in both species. The medium density with four soybean holes achieved the best results, increasing the net photosynthetic rate of tobacco by 30.8% compared with monoculture during the vigorous growth stage. This treatment also enhanced PSII photochemical efficiency, with Fv/Fm and ΦPSII values both higher than other treatments, and chlorophyll a content increased by 32.9% compared with high-density intercropping. The activities of Rubisco and nitrate reductase rose by 18.8% and 49.2%, respectively. At the same time, this density reduced the incidence of tobacco black shank disease and increased salicylic acid and jasmonic acid contents by 38.9% and 33.7%. Peroxidase, superoxide dismutase, and phenylalanine ammonia-lyase activities were also elevated. Tobacco leaves under this treatment showed a balanced chemical composition with high sugar, high potassium, and low chlorine contents, resulting in superior flue-cured quality and the highest economic return.ConclusionThe four-hole soybean density optimized photosynthesis, nitrogen metabolism, and defense responses, improving tobacco quality and yield. These findings provide a physiological and agronomic basis for developing efficient and sustainable tobacco–soybean intercropping systems.